Basic & Clinical pharmacology - Katzung, Bertram G.; Masters, Susan B.; Trevor, Anthony J. (McGraw Hill Medical, 2009)
Organized to reflect the syllabi in Pharmacology courses, Basic & Clinical Pharmacology covers all the important concepts students need to know about the science of pharmacology and its application to clinical practice. It is acknowledged worldwide as the field's most current, authoritative, and comprehensive textbook. To be as clinically relevant as possible, the book features a strong focus on the choice and use of drugs in patients and the monitoring of their effects.